Cannabidiol (CBD) Use among children with juvenile idiopathic arthritis - Christopher J Failing; Kevin F. Boehnke; Meredith Riebschleger (BMC, 2021)
Abstract Background Juvenile idiopathic arthritis (JIA) is common and difficult to treat. Cannabidiol (CBD) is now widely available, but no studies to date have investigated the use of CBD for JIA. Methods We performed a chart review to identify patients with JIA at a Midwestern medical institution between 2017 and 2019. We surveyed primary caregivers of JIA patients using an anonymous, online survey with questions on caregiver knowledge and attitudes towards CBD. We compared respondents with no interest in CBD use vs. those contemplating or currently using CBD using descriptive statistics. Results Of 900 reviewed charts, 422 met inclusion criteria. Of these, 236 consented to be sent a survey link, and n=136 (58%) completed surveys. Overall, 34.5% (n=47) of respondents reported no interest in using a CBD product for their child's JIA, while 54% (n=79) reported contemplating using CBD and 7% (n=10) reported currently giving their child CBD. Only 2% of respondents contemplating or actively using a CBD product learned about CBD from their child's rheumatologist, compared with television (70%) or a friend (50%). Most respondents had not talked to their child's rheumatologist about using CBD. Of those currently using CBD, most used oral or topical products, and only 10% of respondents (n=1) knew what dose they were giving their child. Conclusions Our results show infrequent use but a large interest in CBD among caregivers of children with JIA. Given CBD's unknown safety profile in children with JIA, this study highlights a need for better studies and education around CBD for pediatric rheumatologists.